A study on guest turnover in Juta's Hotel - Marrie, Cheesey (2015)
Hotel is a commercial establishment that provides lodgings, meals, and other guest services. It not only focuses on the products but also their services when doing their business. Maintaining and increasing the guest turnover is very important for any organization. Hence, they must understand the factors that can attract more customers and make them satisfy with their services and other factors. It is essential as it will help the hotel to generate more profit to the organization and their image. There are several factors that can influence guest turnover in hotel. Some of them are hotel's attributes like cleanliness, location, room rates, security, service quality, and reputation of the hotel or chain is important in hotel performance (McCleary et al., 1993). Hence, this paper attempts to study the factors that influence guest turnover in Juta's Hotel. The questionnaire distributed in the hotel is 100 and get it back completely. From the study, all the independent variables which are service, price and cleanliness accepted as factors that contribute in guest turnover in Juta's Hotel. Thus, the hypotheses were accepted. In addition, the information from previous study related to guest turnover to hotel can also be used in Juta's Hotel.